Wastewater treatment and emerging contaminants: Bibliometric analysis. (June 2022) - Chen, Yixia; Lin, Mingwei; Zhuang, Dan
Abstract: In recent years, emerging contaminants have been found in the wastewater, surface water, and even drinking water, which should be treated to ensure the safety of our living environment. In this study, we provide a comprehensive summary of wastewater treatment and emerging contaminants research from 1998 to 2021 by using the bibliometric analysis. This study is conducted based on the Web of Science Core Collection Database. The bibliometix R-package, VOSviewer and CiteSpace software are used for bibliometric analysis and science mapping. A dataset of 10, 605 publications has been retrieved. The analysis results show that China has produced the most publications. China and the United States have the closest cooperation. Analysis of the most cited papers reveals that the purification or removal techniques such as ozonation or membrane filtration can effectively remove pharmaceutical compounds from the water environment. We also found that the efficient detection of emerging contaminants and the optimization of removal methods are current challenges. Finally, future research directions are discussed. Graphical abstract: Co-occurrence network of keywords. Image 1 Highlights: 10, 605 publications of wastewater treatment and emerging contaminants were analyzed. China and the United States have the closest cooperation. China, United States, and Spain have the most documents. The publication published by Heberer (2002) receives the most citations. Removal is a popular keyword in this research.